The factors that affect LBW in developing countries - Ilham Permana Akmal; Debby Endayani Safitri; Anna Fitriani (Arsip Keilmuan Gizi (AKG), 2024)
LBW is still one of the health problems in various countries, especially developing countries because it contributes the highest number in the case of Infant Mortality Rate (IMR), there are million babies born with LBW at delivery each year or around 15,5% in the world and 96,5% of them occur in developing countries, many factors can cause LBW. This study aims to identify and synthesize the influence LBW, as well as conclude the gaps in existing theories. This study uses a systematic literature review method. The population and sample in this study were all literature contained in the database that met the criteria, the literature sources came from 3 electronic databases, namely Google Scholar, PubMed and ProQuest using the keywords Low Birth Weight (LBW) or Bayi Berat Lahir Rendah (BBLR). The results showed that nutritional status (Pvalue = 0,004), food variety and quality (RR 0,53), weight gain (Pvalue = 0,003), total cholesterol (Pvalue = 0,027), maternal characteristic (education with Pvalue = 0,006, occupation with Pvalue = 0,001, age with Pvalue = 0,001 and parity with Pvalue = 0,025), socioeconomic (Pvalue = 0,004), pregnancy complications (oligohydramnios with OR 2,10 and preeclampsia with OR 4,752), enviromental factors (smoke exposure with OR 2,219 and air pollution with OR 1,405), and comorbidities (anemia Pvalue = 0,011  and malaria infection OR 2,06) significantly affect the incidence of LBW.